Analisis Risiko Produksi Cabai Rawit di Desa Kiritana Kecamatan Kambera Kabupaten Sumba Timur - Febrika Jekson, Alvalen; Junaedin Wadu (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2025)
The production of bird’s eye chili in East Sumba from 2020 to 2023 exhibited fluctuating trends with a general decline, marked by a significant drop in 2023, indicating the presence of production risks. This study aims to assess the level of production risk in Kiritana Village and to identify the factors influencing both production and its associated risks. The research was conducted in September 2024, involving 35 chili farmers selected through a census method. Data analysis employed the Coefficient of Variation (CV) to measure the level of production risk, the Cobb-Douglas multiple linear regression model to analyze production functions, and the Just and Pope model to examine the risk effects of influencing factors. The findings reveal that the production risk of bird’s eye chili in Kiritana Village falls within a moderate category, with a CV value of 34%. On the other hand, factors such as land size, seeds, pesticide use, and labor are not proven to affect the level of production risk in the study area. Keywords: Chili Pepper, Production, Risk